Pseudocyst of the Psoas: a case report - Darlington, C. Danny; Joseph, S. Carbin; Anitha, G. Fatima Shirly (International Surgery Journal, 2017)
Psoas abscess is usually tuberculous or pyogenic in etiology. Pancreatitis of the tail of pancreas can cause psoas pseudocyst, especially on the left side. Infection of such pseudocysts can mimic pyogenic psoas abscess, and is more common in diabetics. We report a 25-year-old non-diabetic man with acute severe pancreatitis, who developed infected left psoas abscess on follow up. The psoas abscess was managed successfully by percutaneous drainage and antibiotics.